SISTEM PENJAMINAN MUTU INTERNAL DI SD UKHUWAH 2 BANJARMASIN - Muhammad Yuseran (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
SPMI Basic Education is planned, implemented, controlled, and developed by each education unit. The internal quality assurance system is an independent activity carried out by schools as a basis for external quality assurance carried out by the National Accreditation Board for Schools/Madrasahs. This study aims to describe the internal quality assurance management system at SD Ukhuwah 2 Banjarmasin and internal quality indicators at SD Ukhuwah 2 Banjarmasin. In this case the researcher describes the internal quality assurance system at SD Ukhuwah 2 Banjarmasin. The data in this study is the internal quality assurance system at SD Ukhuwah 2 Banjarmasin which consists of establishing, fulfilling, controlling and developing as well as the specificity of internal quality standards at SD Ukhuwah 2 Banjarmasin. The findings in this study are (1) The internal quality assurance system consists of four stages, namely (a) Determination by mapping quality with activities (b) Fulfillment of 8 national education standards and 1 special standard (c) control is carried out by the school principal and the Education Division of the Ukhuwah Foundation referring to the provisions of the quality standard of the Integrated Islamic School Network (JSIT) (d) development is carried out by establishing a new, higher quality standard if school achievements have met the minimum according to the SNP.